2017
DOI: 10.1161/jaha.116.005446
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Stroke in Minor Ischemic Stroke or Transient Ischemic Attack With Metabolic Syndrome and/or Diabetes Mellitus

Abstract: BackgroundWe aimed to determine the risk conferred by metabolic syndrome (METS) and diabetes mellitus (DM) to recurrent stroke in patients with minor ischemic stroke or transient ischemic attack from the CHANCE (Clopidogrel in High‐risk patients with Acute Non‐disabling Cerebrovascular Events) trial.Methods and ResultsIn total, 3044 patients were included. Patients were stratified into 4 groups: neither, METS only, DM only, or both. METS was defined using the Chinese Diabetes Society (CDS) and International Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 34 publications
0
37
0
Order By: Relevance
“…A recent study from China has shown that the incidence of recurrent stroke has increased 3-fold between 1992 and 2012 [3]. Age [4], dyslipidemia [5], smoking [6], diabetes, hypertension, homocysteine levels, atrial fibrillation [1], metabolic syndrome [7] and other risk factors [8][9][10] are associated with recurrent stroke. Indeed, a recent study has shown that hypertension, prior symptomatic stroke and chronic infarcts on MRI were independently associated with recurrent stroke and this also doubled the all-cause mortality [11].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study from China has shown that the incidence of recurrent stroke has increased 3-fold between 1992 and 2012 [3]. Age [4], dyslipidemia [5], smoking [6], diabetes, hypertension, homocysteine levels, atrial fibrillation [1], metabolic syndrome [7] and other risk factors [8][9][10] are associated with recurrent stroke. Indeed, a recent study has shown that hypertension, prior symptomatic stroke and chronic infarcts on MRI were independently associated with recurrent stroke and this also doubled the all-cause mortality [11].…”
Section: Introductionmentioning
confidence: 99%
“…Minor stroke and transient ischemic attack (TIA) are usually regarded as a whole to study because of the similar pathophysiological mechanism and epidemical characteristics . It is reported that minor ischemic stroke and TIA account for ≈65% of all acute ischemic cerebrovascular events . Although minor stroke and TIA seem to be benign, recent studies have shown that a significant proportion of patients with steno‐occlusive arterial disease is in unstable clinical state and has high risks of recurrent cerebrovascular events or early neurological deterioration (END) in the hospital, resulting in major physical disability .…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al found that there was a significant difference between systolic blood pressure and the NIHSS value of acute stroke patients, where patients with higher systolic blood pressure had higher NIHSS values, but different results found in diastolic blood pressure. 5,11 Kvistad et al reported that elevated admission blood pressure was associated with mild stroke and severe stroke. 12 We also found no significant difference in HSP 70 levels in the mild stroke group as compared to that of a moderate stroke group.…”
Section: Discussionmentioning
confidence: 99%